Small Annexin V–Positive Platelet-Derived Microvesicles Affect Prognosis in Cirrhosis: A Longitudinal Study. Issue 5 (28th May 2021) - Weil, Delphine; Di Martino, Vincent; Mourey, Guillaume; Biichle, Sabeha; Renaudin, Adeline; Laheurte, Caroline; Cypriani, Benoit; Delabrousse, Eric; Grandclément, Emilie; Thévenot, Thierry; Saas, Philippe; ,
Abstract : INTRODUCTION: Microvesicles (MVs) with procoagulant properties may favor liver parenchymal extinction, then cirrhosis-related complications and mortality. In a longitudinal cohort of cirrhotic patients, we measured plasma levels of platelet-derived MVs (PMVs), endothelial-derived MVs, and red blood cell–derived MVs, expressing phosphatidylserine (annexin V–positive [AV + ]) or not, and evaluated their impact on Model for End-Stage Liver Disease (MELD) score and transplant-free survival. METHODS: MVs were quantified using flow cytometry in plasma from 90 noninfected cirrhotic patients and 10 healthy volunteers matched for age and sex. Impact of plasma microvesicle levels on 6-month transplant-free survival was assessed using log-rank tests and logistic regression. RESULTS: Microvesicle levels, mostly platelet-derived, were 2.5-fold higher in healthy volunteers compared with cirrhotic patients. Circulating small AV + PMV levels were lower in cirrhotic patients ( P = 0.014) and inversely correlated with MELD scores ( R = −0.28; P = 0.0065). During 1-year follow-up, 8 patients died and 7 underwent liver transplantation. In the remaining patients, circulating microvesicle levels did not change significantly. Six-month transplant-free survival was lower in patients with low baseline small AV + PMV levels (72.6% vs 96.2%; P = 0.0007). In multivariate analyses adjusted for age, ascites, esophageal varices, encephalopathy, clinical decompensation, total platelet counts, MELD score, and/or Child-Pugh C stage, patients with lower small AV + PMV levels had a significant 5- to 8-fold higher risk of 6-month death or liver transplant. Other PMV levels did not impact on survival. DISCUSSION: Decreased circulating small AV + PMV levels are associated with significantly lower transplant-free survival in cirrhotic patients independently of MELD score and platelet counts.